Introduction to landscape architecture - Conner, Marvin (Forest Hills, NY Callisto Reference, 2023)
Landscape architecture is involved in the designing of outdoor areas, landmarks and structures in order to achieve environmental and social-behavioral outcomes. It focuses on the systematic investigation of the processes of the landscape as well as the social, ecological and soil conditions. It also focuses on the design of interventions to produce the desired outcome. Some of the various aspects which are dealt with under this discipline are site planning, stormwater management, erosion control, environmental restoration, landscape design, and parks and
recreation planning. It is also an important contributor to urban design, pedestrian schemes, waterfronts and city squares. This book is a compilation of chapters that discuss the most vital concepts in the field of landscape management. While understanding the long-term perspectives of the topics, the book makes an effort in highlighting their impact as a modern tool for the growth of the discipline. It is an essential guide for both academicians and those who wish to pursue this discipline further.-back cover
Keywords: Landscape architecture; Landscape gardening; Sustainable design